2007
DOI: 10.1111/j.1440-1754.2007.01199.x
|View full text |Cite
|
Sign up to set email alerts
|

Mothers of pre‐school children talk about childhood overweight and obesity: The Weight of Opinion study

Abstract: The emotional intensity of the mothers' perceptions about their children's eating and weight status suggests that interventions, including communications, need to go beyond information and engage with parents' emotions. Some food concerns were actually related to broader parenting issues and indicate the potential value for interventions to focus on behavioural parenting techniques. Preventive interventions need to acknowledge the issues faced by parents and support their role directly, such as through making … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
93
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(102 citation statements)
references
References 13 publications
8
93
0
1
Order By: Relevance
“…Previous literature has identified negative outcomes of restrictive feeding practices: increasing the consumption of restricted foods, eating in the absence of hunger, and the high vulnerability of obesity [36][37][38][39]. Concerned mothers of overweight children are likely to use restrictive feeding practices with their child [17,33,39]. While mothers using restrictive feeding practices were not concerned about weight in the present study, participants frequently reported use of restrictive feeding practices with their children.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Previous literature has identified negative outcomes of restrictive feeding practices: increasing the consumption of restricted foods, eating in the absence of hunger, and the high vulnerability of obesity [36][37][38][39]. Concerned mothers of overweight children are likely to use restrictive feeding practices with their child [17,33,39]. While mothers using restrictive feeding practices were not concerned about weight in the present study, participants frequently reported use of restrictive feeding practices with their children.…”
Section: Discussionmentioning
confidence: 57%
“…Improper feeding practices may endanger children for eating disorders or may lead to overfeeding or underfeeding [12][13][14][15]. For example, preventing children from eating a restricted food can make them consume more of that food, and forcing them to eat can foster a distaste of that food [14,16,17]. …”
Section: Introductionmentioning
confidence: 99%
“…One possible explanation is that parents of children of this age think their child has 'puppy fat' and is something that they 'will grow out of'. While not examining identification of weight status, Pagnini et al (8) reported that mothers of preschool-aged children were more concerned about their child being underweight than overweight. Child obesity campaigns may need to focus efforts on parents of very young children in order to challenge this pattern of thinking.…”
Section: Parental Perceptions Of Their Child's Weight Statusmentioning
confidence: 99%
“…Parents report the need for support in overcoming skill and knowledge barriers (13)(14)(15)(16) in order to facilitate healthy eating behaviours in their children. Methods of providing parental support that are effective in increasing fruit and vegetable consumption, that can be feasibly delivered to a large number of parents at a relatively low cost and that are considered acceptable to parents represent public health approaches likely to benefit children's nutrition (17) .…”
mentioning
confidence: 99%